(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Backrgound: Enhancing methods for decellularization of animal corneas for the development of bioengineered corneal models with the following keratoplasty makes it possible to overcome the shortage of human donor material. Purpose: To investigate the clinical efficacy of intralamellar keratoplasty (IKP) with corneal stromal substitutes (CSSs) developed using different decellularization methods in the animal study. Materials and Methods: Corneas were excised from enucleated pig eyes, and, to develop acellular CSSs, five methods of decelluarization of porcine corneas were used that were different in the time and conditions of incubation with detergents (0.5% sodium dodecyl sulphate or TRITON X-100) and proteolytic enzymes (like 0.1% papain). In addition, an ultrasonic apparatus of type СD 3800 А was used to further improve the removal of cells and acellular corneal debris. A total of 40 Chinchilla rabbits were used in the animal study. They were divided into 5 groups with different CSS versions. In each rabbit, the monocular IKP was carried out with one of the five CSS versions. Postoperatively, antimicrobial and anti-inflammatory therapy was instituted. Animals were examined every other day for 30 days postoperative. This included corneal fluorescein staining. In addition, the following was assessed ophthalmoscopically: conjunctival discharge, conjunctival hyperemia, state of the CSS, state of the host cornea, and, at late follow-up examinations, graft acceptance and whether graft-versus-host disease was present. Results: In rabbit eyes that underwent IKP with a version 4 CSS, the clinical scores for conjunctival discharge, corneal graft edema, inflammatory infiltration, corneal graft opacity and corneal fluorescein staining (0.13 points) were statistically significantly lower than in eyes that underwent IKP with other CSS versions. Location of inflammation in the cornea was found to be paracentral in eyes that improved clinically after IKP with version 1, 2, 3 or 5 CSS, and tended to be central (0.38 points) in those that underwent IKP with a version 4 CSS. Conclusion: The least apparent reaction was noted in the rabbit eyes that underwent IKP with a version 4 CSS, which makes this CSS promising for further investigations in pre-clinical and clinical studies.